Crimes of war : what the public should know - Gutaman, Roy (ed.) (New York, 1999)
We see and read about brutal and seemingly senseless warfare in the news every day --Rwanda, Bosnia, Chechnya, to name a few. This A-to-Z guidebook reveals --through case studies, definitions of key terms, and explanations of what's legal and what's not --what the public needs to know about war and the law. Laws of war exist. They define and categorize those acts of signal cruelty and murder that are universally known as war crimes. The laws of war have never been more developed, yet never before have so many innocent civilians been the victims of war crimes. It is clear that the laws are not being adhered to, nor have these laws been brought to light for the public or the journalists reporting on conflicts. Crimes of War is a timely and important book, especially in light of the recent creation of the United Nations International Criminal Tribunal to try war criminals in Rwanda and Bosnia and the development of a permanent International Criminal Court. Authors Sidney Schanberg and Peter Maass, reporters Tom Gjelton from NPR and Roger Cohen from the New York Times, and photojournalists Gilles Peress and Susan Meiselas, along with many other award-winning writers and photographers, have contributed to this powerful book. The 145 entries define terms from Armistice to Wanton Destruction as well as give case studies of recent and ongoing conflicts.
Keywords: War crimes